1998
DOI: 10.1097/00005768-199805000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and health-related fitness in youth: amultivariate analysis

Abstract: There is a significant relationship between activity and health-related physical fitness, but a large part of the variability (80-90%) in fitness is not accounted for by physical activity as measured in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
63
2
8

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 12 publications
11
63
2
8
Order By: Relevance
“…In agreement with our findings, some other studies could not confirm a negative association between PA and body fatness (36,37) or found that underweight adolescents were less likely to be physically active (10) .…”
Section: Discussionsupporting
confidence: 82%
“…In agreement with our findings, some other studies could not confirm a negative association between PA and body fatness (36,37) or found that underweight adolescents were less likely to be physically active (10) .…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, Katzmarzyk et al 32 analyzed 356 boys and 284 girls (9-18 years) from the Québec Family Study and found a weak association between PA and static strength of the legs in a maximal voluntary isometric contraction at a knee angle of 90° and a low no significant association between PA and sum of 6 skinfolds. Ara et al 18 showed in 114 prepubertal boys (9.4±1.5 years) that participation in at least 3 hours per week of extracurricular physical activities and sport competitions was associated with higher squat jump performance and lower fat mass levels compared with non-participants.…”
Section: Discussionmentioning
confidence: 98%
“…In this case, the daily activities are classified in a continuum involving nine categories, according to estimates concerning mean caloric cost of the activities performed by humans: (1) rest in bed; (2) activities performed at sitting position; (3) mild activities performed at standing position; (4) activities which involve mild walks (< 4 km/ hour); (5) mild hand labor; (6) active leisure activities and practice of recreational sports; (7) moderate hand labor; (8) active leisure activities and moderate sports practice; and (9) intense hand labor and practice of competitive sports. Since it is practical, innocuous and easy to be interpreted, the present instrument has been widely accepted and used in other studies involving young populations (25,(35)(36)(37)(38) . The retrospective instrument was filled out by the adolescents themselves in four days of the same week, two in the middle (between Monday and Friday) and two on the weekend (Saturday and Sunday).…”
Section: Methodsmentioning
confidence: 99%